2008
DOI: 10.1097/pdm.0b013e3181656d67
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Estrogen Receptor β in Colon Cancer Progression

Abstract: Colon cancer is the most frequent neoplasia of the intestine. This pathology is the third highest cause of death from cancer with 430,000 deaths globally per year. Estrogen has also been implicated in the development and progression of colon cancer. Also sex-specific differences have been suggested to be involved in the process. Previous studies have shown the estrogen b receptor to be the dominant receptor type in normal colonic tissue and its down-regulation along with the progression of colorectal cancer. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 29 publications
(27 reference statements)
1
31
0
Order By: Relevance
“…Apart from ovarian cancer, ERb has been implicated in the carcinogenesis of various other malignancies including prostate cancer (Attia & Ederveen 2012), colorectal cancer (Castiglione et al 2008), and cholangiocarcinoma (Marzioni et al 2012). The development of very selective ERb agonists has been very promising in recent years (Mohler et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from ovarian cancer, ERb has been implicated in the carcinogenesis of various other malignancies including prostate cancer (Attia & Ederveen 2012), colorectal cancer (Castiglione et al 2008), and cholangiocarcinoma (Marzioni et al 2012). The development of very selective ERb agonists has been very promising in recent years (Mohler et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Other groups have shown that ERbKO mice are more susceptible to inflammation-associated colon cancer than the WT mice (Saleiro et al 2012). Clinical and experimental models of colonic carcinogenesis have suggested that the protein expression of ERb decreases as the tissues progress from a normal colonic epithelial to a malignant state (Konstantinopoulos et al 2003, Castiglione et al 2008, Di Leo et al 2008, Mostafaie et al 2009). In fact, humans with colon tumors not expressing ERb are likely to be in more advanced stages of cancer and have a higher risk for death compared with those with tumors in which ERb is present (Rudolph et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It has been consistently reported that men have slightly higher rates of bile duct cancer than women (1); reasons for this are unclear but may be due to differences in prevalence of smoking, infection, occupational exposure or hormone-related factors between men and women (1,6). While ESRs have been more studied in women, they have also been linked to certain diseases in men, including cancers of the prostate and colon (31)(32)(33). In addition, in a study of ESR polymorphisms and plasma lipid levels, ESR1 variants, rs9322331 and rs9340799, were more strongly associated with apolipoprotein C in men but were more strongly associated with triglycerides in women, suggesting that ESR1 variation has sex-dependent effects on circulating lipid levels (33).…”
Section: Discussionmentioning
confidence: 99%